The didactic laboratory, essential source to fracture exclusion barriers: Inclusive education - Grijalba Obando, John Jairo; Orozco Buelvas, Deisy (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The need to move from idealized theories and legal frameworks to practical and real measures that can be lived in school, constitute one of the most significant barriers when it comes to achieving inclusive education; Therefore, practical scenarios such as laboratories are spaces that allow the construction of new tools, breaking down these exclusionary barriers from an approach focused on good practices. In accordance with the above, the research aims to recognize the understandings and practices that have emerged from Latin America within the framework of didactic laboratories for education.